THE EFFECT OF THE SNOWBALL DRILLING LEARNING METHOD ON JAVANESE LANGUAGE LEARNING MOTIVATION OF THIRD GRADE STUDENTS AT SD NEGERI 1 BULUNGAN - Nambella Septi Prasetya; Dwiana Asih Wiranti (PGMI Fakultas Tarbiyah Universitas Islam Jember, 2026)
Learning Javanese language in elementary schools plays a strategic role in preserving culture and enhancing students’ language skills. This study aims to examine the effect of the Snowball Drilling method on the learning motivation of third-grade students at SD Negeri 1 Bulungan. This research employed a quantitative method with a pre-test and post-test design involving 28 students. Prerequisite tests included instrument validity and normality tests. The hypothesis was tested using a paired sample t-test. The results showed an increase in learning motivation after implementing the Snowball Drilling method, with the average pre-test score of 68.8 rising to a post-test score of 79.7. The paired sample t-test analysis yielded a significant value (p < 0.05), indicating a positive effect of the Snowball Drilling method on students’ learning motivation. These findings confirm that Snowball Drilling is effective not only in improving learning outcomes but also in fostering a participative and enjoyable learning environment.